2021
DOI: 10.1111/brv.12757
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the causes and consequences of cooperative behaviour in wild animal populations using a social network approach

Abstract: Understanding why individuals carry out behaviours that benefit others, especially genetically unrelated others, has been a major undertaking in many fields and particularly in biology. Here, we focus on the cooperation literature from natural populations and present the benefits of a social network approach in terms of how it can help to identify and understand factors that influence the maintenance and spread of cooperation, but are not easily captured when solely considering independent dyadic interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 182 publications
(225 reference statements)
2
11
0
5
Order By: Relevance
“…Interestingly, we also found that participation in mobbing was more sensitive to the potential costs of participation than the potential benefits of success. Furthermore, our finding that long-term social ties were associated with mobbing supports theoretical work demonstrating the importance of social network connections to successful group cooperation 16,17 . Importantly, our work adds a third critical component to successful collective action: short-term prosocial behaviors.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, we also found that participation in mobbing was more sensitive to the potential costs of participation than the potential benefits of success. Furthermore, our finding that long-term social ties were associated with mobbing supports theoretical work demonstrating the importance of social network connections to successful group cooperation 16,17 . Importantly, our work adds a third critical component to successful collective action: short-term prosocial behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…Theoretical modelling suggests that group members are more likely to participate when they can expect the biggest share of the benefits or rewards, can contribute for the lowest cost, or are the most capable (e.g., largest, strongest) 14,15 . Other theoretical studies have demonstrated the importance of social network connections to successful collective action, especially in societies where social relationships are critical to fitness 16,17 . However, empirical studies about collective action within heterogenous animal groups are still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real life, power and affiliation have been identified as two main factors for social relations 26 31 and two important goals that an individual could have irrespective of their demography, culture or wealth 32 . Further, quickly assessing the social status (i.e., power) and kinship (i.e., affiliation) of others is an important basis for survival and reproduction of social animals 33 .
Figure 1 Experimental design.
…”
Section: Introductionmentioning
confidence: 99%
“…image-scoring or reciprocity 75]. Tibbetts & Dale [1] note that individual recognition is particularly important when "there are repeated interactions among multiple individuals with differing intentions" which is exactly the case in most settings where cooperation arises; cooperation (especially among non-kin) is most likely to occur when there are stable social structures and heterogenous interactions [76][77][78].…”
Section: Cooperation and Individual Recognitionmentioning
confidence: 99%